Acting for animators - Hooks, Ed (Routledge, 2011)
"Ed Hooks' indispensable acting guidebook for animators returns. Ed uses basic acting theory to explain everything from character movement and facial expressions to interaction and scene construction. Just as acting on film and on stage are very different disciplines, so is the use of acting theory in creating an animated character, scene or story.New to this Routledge edition:- illustrated, scene-by-scene analyses of six films, including Up, Coraline and Kung Fu Panda- an expanded chapter on video game animation- all-new illustrations- a history of acting in 500 words"--Vydavatelská anotace
Název z titulní obrazovky
Keywords: animované filmy; filmová animace; animated films; film animation; příručky; elektronické knihy; handbooks, manuals, etc; electronic books